Integrasi Model PBL, STEAM, kontekstual dan media geomath: meningkatkan pemecahan masalah dan berpikir kreatif siswa - Rahmi, Ruaida; Rini, Tika Puspita Widya (Papanda Journal of Mathematics and Science Research, 2025)
Low learning activities, problem-solving abilities, creative thinking, and student learning results in mathematics are the driving forces behind this study. This study aims to explain how the use of Problem Based Learning, STEAM, Contextual models, and GeoMath media can enhance teacher and student activities, problem-solving abilities, creative thinking, and student learning results. Ten third-grade students from UPTD SDN 1 Kurau Utara participated in four meetings for this Classroom Action Research (CAR) study during the 2024–2025 school year. Tests and observation were utilized in the data gathering methods, and the results were descriptively analyzed. Teacher activity (score 24–28), student activity (50% to 90%), problem-solving abilities (40% to 90%), creative thinking (30% to 90%), and student learning outcomes (40% to 50% to 90%) all increased, according to the study's findings. As a result, using GeoMath media, Problem Based Learning, STEAM, and contextual models effectively enhances student engagement and learning results in mathematics.